2019
DOI: 10.3389/fvets.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Intake and Long-Term Effects of Essential Oils After a Negative Postnatal Experience in Chicks

Abstract: The postnatal period is critical for broiler chicks as they are exposed to potentially stressful environmental changes in the hatchery and during transportation to the rearing houses. The ability of broiler chicks to spontaneously drink essential oils (EO) to mitigate the effects of a negative postnatal experience was tested. Chicks were placed in the rearing facility either immediately (C group), or after a 24 h-delay period (D group) to mimic a delay in transportation possible under commercial conditions. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 49 publications
0
7
0
5
Order By: Relevance
“…This study presents immediate and long-lasting effects of a delayed placement of chickens considered as a negative postnatal experience, mimicking early-life stresses encountered in poultry production, and the potential beneficial effects of EO intake on blood physiological parameters and gene expression profiling of chicken blood cells. In a previous study, we showed that chicks spontaneously chose to consume EO or not, according to their postnatal experience when different EO were presented individually 10 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study presents immediate and long-lasting effects of a delayed placement of chickens considered as a negative postnatal experience, mimicking early-life stresses encountered in poultry production, and the potential beneficial effects of EO intake on blood physiological parameters and gene expression profiling of chicken blood cells. In a previous study, we showed that chicks spontaneously chose to consume EO or not, according to their postnatal experience when different EO were presented individually 10 .…”
Section: Discussionmentioning
confidence: 99%
“…MEF2A is also known to influence muscle development and has been described in chicken 26 . Thus the MEF2A pathway may be activated to counter the observed decrease in P. major muscle yield observed in the Delayed chick group 10 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the thermoregulatory system of chicks is immature at hatching ( Tzschentke, 2007 ), they remain very sensitive to postnatal cold temperatures during the first days of breeding ( Collin et al., 2003 , Mujahid and Furuse, 2009 ). Environmental conditions during the perinatal period are considered critical for later performance and fitness of chickens ( Guilloteau et al., 2019 ). Especially, brooding chicks at low temperatures (26.7°C vs. 32.2°C) results in a decreased feed efficiency and increased mortality rate ( Renwick and Washburn, 1982 ).…”
Section: Introductionmentioning
confidence: 99%